COLLABORATION OF ACTORS IN THE NETWORK IN STUNTING PREVENTION PROGRAMS IN BULUKUMBA DISTRICT - Leli Herlianti (Institute of Computer Science (IOCS), 2022)
The purpose of this study aims to analyze the collaboration of actors in the network in the stunting prevention program in Bulukumba district using qualitative research methods. The data collection method is by observation and document study. The data analysis method is data condensation, data presentation and conclusion drawing. The results of data analysis show that the number of children with stunting in Bulukumba district is 1740 cases spread over 20 sub-districts and there are 58 people scattered in various regional apparatus organizations in Bulukumba who are members of the stunting prevention team including the Health Office, Development Planning Agency, Regional Research and Development, Population control agency, family planning, Women's Empowerment and Child Protection, and others. Collaboration between actors in the network, such as face-to-face dialog, is carried out through stunting consultations and is stated in the MOU on the equality of stunting data and the commitment of the actors in stunting prevention programs.